2002
DOI: 10.1038/sj.cr.7290128
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted neuronal precursors migrate and differentiate in the developing mouse brain

Abstract: The subventricular zone (SVZ), lining the lateral ventricle in forebrain, retains a population of neuronal precursors with the ability of proliferation in adult mammals. To test the potential of neuronal precursors in adult mice, we transplanted adult SVZ cells labeled with fluorescent dye PKH26 into the lateral ventricle of the mouse brain in different development stages. The preliminary results indicated that the grafted cells were able to survive and migrate into multiple regions of the recipient brain, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Several studies have shown that the intrinsic mechanisms determining the restricted potential of progenitors to form restricted lineage of neurons is an important character of stem cells in the nervous system (Barbe and Levitt, 1991;Frantz and McConnell, 1996;Suhonen et al, 1996;Desai and McConnell, 2000;Shihabuddin et al, 2000;Seidenfaden et al, 2000). However, when stem cells from one neurogenic region is transplanted into other neurogenic regions, transplanted cells can acquire new fates and give rise to the type of neurons in the recipient region (Lim et al, 1997;Clarke et al, 2000;Temple, 2001;Peng et al, 2002). This suggests that the intrinsic mechanisms can be overridden under certain circumstances, which are likely to depend on the combination of cell-intrinsic and extrinsic factors (Temple, 2001;Merkle et al, 2007;Alvarez-Buylla et al, 2008;Costa et al, 2010;Ma et al, 2010).…”
Section: Stem/progenitor Cells In the Adult Vertebrate Brain Adult Nementioning
confidence: 94%
“…Several studies have shown that the intrinsic mechanisms determining the restricted potential of progenitors to form restricted lineage of neurons is an important character of stem cells in the nervous system (Barbe and Levitt, 1991;Frantz and McConnell, 1996;Suhonen et al, 1996;Desai and McConnell, 2000;Shihabuddin et al, 2000;Seidenfaden et al, 2000). However, when stem cells from one neurogenic region is transplanted into other neurogenic regions, transplanted cells can acquire new fates and give rise to the type of neurons in the recipient region (Lim et al, 1997;Clarke et al, 2000;Temple, 2001;Peng et al, 2002). This suggests that the intrinsic mechanisms can be overridden under certain circumstances, which are likely to depend on the combination of cell-intrinsic and extrinsic factors (Temple, 2001;Merkle et al, 2007;Alvarez-Buylla et al, 2008;Costa et al, 2010;Ma et al, 2010).…”
Section: Stem/progenitor Cells In the Adult Vertebrate Brain Adult Nementioning
confidence: 94%
“…Mammalian adult neurogenesis takes place predominantly via the NSCs confined to two distinct parts of the forebrain, i.e., the subventricular zone (SVZ) of the lateral ventricles in the telencephalon and the subgranular zone (SGZ) of the dentate gyrus in the hippocampus ( Alvarez-Buylla et al, 2001 ; Kriegstein and Alvarez-Buylla, 2009 ; Bonfanti and Peretto, 2011 ). The restricted capacity of the neurogenic niches is explained partially by the reduction of constitutively active adult proliferation zones in mammalian brain during evolution ( Rakic, 2002 ; Lindsey and Tropepe, 2006 ; Tanaka and Ferretti, 2009 ), a specific or general resistance against cell proliferation due to the evolution of tight control mechanisms against tumorigenesis ( Pearson and Sanchez Alvarado, 2008 ), resistance to integrate new cells into a mature neural network ( Kempermann et al, 2004 ; Kaslin et al, 2008 ), an altered cellular plasticity that affects stem or progenitor cell characteristics ( Shihabuddin et al, 2000 ; Peng et al, 2002 ; Kizil et al, 2012b ), or a non-permissive environment related to scar formation at the wound site after injury ( Ekdahl et al, 2003 ; Fitch and Silver, 2008 ; Rolls et al, 2009 ). Low neurogenecity is paralleled by a limited potential in the integration of the newborn neurons in most regions of the mammalian brain, necessitating the use of another platform free of these constraints for the development of new therapeutic approaches ( Bhardwaj et al, 2006 ; Ernst and Frisen, 2015 ; Alunni and Bally-Cuif, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, functional integration of this kind of graft is not easy (see above). Neural precursors, on the other hand, have mostly been shown to fail in adopting the specific cerebellar phenotypes to be substituted or in completing neuronal differentiation at all [ 71 , 72 , 81 , 86 ] despite the fact that they are able to migrate into the cerebellum even after injection into the lateral ventricle [ 95 ]. The differentiation of these cells might depend on both the local niche and their origin.…”
Section: Mechanisms Of the Effect Of The Graftsmentioning
confidence: 99%